Relação entre a disartria, saúde mental e qualidade de vida de pessoas com esclerose lateral amiotrófica - Nunes, Renata Lígia Lima Batista (2023)
Amyotrophic Lateral Sclerosis (ALS) is a neurodegenerative disease, which leads to weakness of muscles throughout the body, compromising vital functions, including speech. In addition to the impact on physical health, the mental health and quality of life of people affected by the disease is strongly affected. Therefore, an interdisciplinary approach is necessary to guarantee the quality of life of these individuals, as there is no cure for the disease. This Dissertation is divided into two articles. Article 1 is entitled “Voice changes and associated factors in patients with Amyotrophic Lateral Sclerosis (ALS)”, whose objective was to verify whether there is a correlation between the time of diagnosis, disease progression, peak cough flow, vocal handicap and presence of vocal/speech alterations in patients with ALS. This is a secondary, observational, cross-sectional study using a LIEV database, where data related to the questionnaires were collected: “Vocal Disadvantage Index (IDV-10)” and “Sclerosis Functional Assessment Protocol Amyotrophic Lateral (ALFRS-R)”. A speech sample was collected for subsequent auditory-perceptual judgment (JPA) evaluation and the results of the “Peak Flow” exam. Patients diagnosed with ALS participated, most of them male and of the appendicular type. He found that patients with ALS have disadvantages and vocal changes, changes in peak cough flow, and that there is a correlation between the time of diagnosis and the presence of vocal changes in these patients. Article 2 entitled “Assessment of dysarthrias and mental disorders in patients with ALS”, aimed to investigate whether there is an impact on the voice, speech, mental disorders and quality of life of individuals with Amyotrophic Lateral Sclerosis (ALS), as well as verifying whether there is relationship between self-perceived quality of life and mental disorders with clinical variables in individuals with ALS. There was a significant association between GG, pitch, loudness and speech intelligibility in the JPA and the presence of ALS (Table 2). There was no statistical difference when comparing the acoustic data (Fo, jitter, shimmer, HNR, CPPS) of the groups (Table 1) and no significant association between the presence of ALS and the other perceptual-auditory variables (roughness, breathiness, asthenia and tension) (Table two). There was no statistical significance in the correlation analyzes between SRQ-20 and VcD and clinical variables, which also includes JPA and acoustic measurements (Table 3). Patients with ALS have compromised quality of life and mental health, as well as vocal changes resulting from dysatric changes when compared to healthy individuals. A significant association was also observed between the general degree of vocal deviation intensity, pitch, loudness and speech intelligibility and the presence of ALS.